How does social media marketing enhance brand loyalty?identifying mediators relevant to the cinema context - Yee, Wong Foong; Seng, Kaixin; Lim, Xin Jean; Rathakrishnan, Thanuja (Palgrave Macmillan, 2021)
Social media has created a new norm for organizations to engage with their consumers and expand their businesses. In view of this, brand loyalty as an outcome of social media marketing has been acknowledged as a central theme in building long-term consumer relationships. This study focuses on this issue by exploring multiple mediators between social media marketing (SMM) and brand loyalty in the context of cinemas. An online questionnaire was distributed to a sample of 270 cinema goers who were also social media users, in Malaysia. The results of the PLS-SEM analysis revealed that brand satisfaction, brand relationship quality, brand consciousness and value consciousness are significant mediators that impact the relationship between SMM and brand loyalty. Finally, the implications of this study and directions for future research are discussed.